Inter-arm blood pressure differences compared with ambulatory monitoring: a manifestation of the 'white-coat' effect? - Martin, U; Holder, R; Hodgkinson, J; Mcmanus, R (2013)
BACKGROUND: Inter-arm difference in blood pressure of >10 mmHg is associated with peripheral vascular disease, but it is unclear how much of the difference in sequential right and left arm blood pressure measurements might be due to a 'white-coat' effect. AIM: To use ambulatory blood pressure monitoring (ABPM) to better understand the clinical significance of inter-arm differences in blood pressure. DESIGN AND SETTING: Retrospective study in a teaching hospital in Birmingham. METHOD: Anonymised clinical data collected from 784 patients attending a single hospital-based hypertension clinic were retrospectively analysed. Each participant had blood pressure measured sequentially in both arms, followed by ABPM over the subsequent 24 hours. RESULT: Data were available for 710 (91%) patients, of whom 39.3% (279) had a blood pressure difference of 10 mmHg or more between each arm. Compared to daytime systolic ABPM, the difference was 25.1 mmHg using the arm with the highest reading, but only 15.5 mmHg if the lower reading was taken (mean difference 9.6 mmHg (95% confidence interval [CI] = 9.0 mmHg to 10.3 mmHg)). However, differences between mean right (20.7 mmHg) or left (19.9 mmHg) arm blood pressure and daytime systolic ABPM were very similar. CONCLUSION: Compared with ABPM, use of the higher of the left and right arm readings measured sequentially appears to overestimate true mean blood pressure. As there is no significant difference in the extent of disparity with ABPM by left or right arm, this is unlikely to be due to arm dominance and may be due to the 'white-coat' effect reducing blood pressure on repeated measurement. Where a large inter-arm blood pressure difference is detected with sequential measurement, healthcare professionals should re-measure the blood pressure in the original arm.